USE OF FORESIGHT ANALYSIS TERMINOLOGY AS AN APPLIED COMPONENT OF FOREIGN LANGUAGE EDUCATION - Муравйова, Олена; Архипова, Вікторія; Колесник, Аліна; Мануєнкова, Олена; Крупей, Михайло (SWorldJournal, 2025)
The article considers the importance of using interdisciplinary terminology in the process of learning a foreign language, which allows to significantly deepen the understanding of the material and expand vocabulary. The authors emphasize the importance o